Creation of opinion and perception about China in Western social networks - Fernández Fernández, Maximiliano (2019)
This paper proposes to explain the perception about China and the opinion making in Western social networks. It explores the most commented news (in BuzzSumo) in 2017. Through quantitative and qualitative analysis content, shares, commented and likes are quantified; positive and negative perception indicators are measured; the most repeated words (Wordclouds.com) are selected, and the texts are analysed and interpreted. The monitoring of network users (graphs theory and Gelphi) shows the relationship among them. The triangulation of methods and sources is completed with a survey. As a result, the perception about China on the social networks varies depending on the subject and on the distance. The users show concern about the economic and military power of China, but they consider the Chinese population as peaceful, collaborative and hard-working. The social networks operate as a real social brain, in which the most active users contribute to the debate and opinion.